2007
DOI: 10.1007/s00270-006-0226-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Nonrandomized Trial of Manual Compression and Angio-Seal and Starclose Arterial Closure Devices in Common Femoral Punctures

Abstract: We compared the use of manual compression and Angio-Seal and Starclose arterial closure devices to achieve hemostasis following common femoral artery (CFA) punctures in order to evaluate safety and efficacy. A prospective nonrandomized, single-center study was carried out on all patients undergoing CFA punctures over 1 year. Hemostasis was achieved using manual compression in 108 cases, Angio-Seal in 167 cases, and Starclose in 151 cases. Device-failure rates were low and not significantly different in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 27 publications
6
47
1
Order By: Relevance
“…It may be assumed that arterial closure devices may be useful in women with severe coagulation abnormalities, but their use has not been specifically reported in TAE for PPH [61].…”
Section: Vascular Approachmentioning
confidence: 98%
“…It may be assumed that arterial closure devices may be useful in women with severe coagulation abnormalities, but their use has not been specifically reported in TAE for PPH [61].…”
Section: Vascular Approachmentioning
confidence: 98%
“…The recently introduced StarClose vascular closing device, in contrast, completes a circumferential extravascular puncture closure [3]. Prospective randomized, as well as observational studies have demonstrated safety and efficacy of the system in subjects undergoing diagnostic and interventional arterial catheterizations [3][4][5]. Duplex ultrasound examinations found no statistical differences in access site complications between the StarClose 1 and manual compression groups [6].…”
Section: Discussionmentioning
confidence: 96%
“…In the interventional arm of the CLIP study [1], major vascular complications occurred in 1.1% of StarClose subjects. Ratnam et al [3] reported 3 major complications (1.9%) in their StarClose group, which included a pseudoaneurysm requiring thrombin injection, a large hematoma which required blood transfusion and surgical evacuation, and an ischemic ipsilateral lower limb 2 days later which led to a femoro-femoral crossover graft for external iliac artery occlusion. Of interest, they excluded patients for StarClose with artery diameters <6 mm.…”
Section: Discussionmentioning
confidence: 97%